2020
DOI: 10.1007/s12094-020-02483-8
|View full text |Cite
|
Sign up to set email alerts
|

ABVD and BEACOPP regimens’ effects on fertility in young males with Hodgkin lymphoma

Abstract: Purpose Considering the increased cancer patient survivorship, the focus is now on addressing the impacts of treatment on quality of life. In young people, altered reproductive function is a major issue and its effects in young males are largely neglected by novel research. To improve clinician awareness, we systematically reviewed side effects of chemotherapy for Hodgkin lymphoma (HL) in young males. Methods The review was prospectively registered (PROSPERO N. CRD42019122868). Three databases (Medline via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…ABVD or BEACOPP regimens alone are very effective against blood cancer malignancies, yet, their further development is still needed. Evidence suggests that these regimens could negatively impact the fertility of both male and female patients [ 100 , 101 ]. In addition, Ramos et al reported that the ABVD regimen induces genomic chaos after one year of the treatment.…”
Section: Combination Of Vincristine With Procarbazine or Dacarbazinementioning
confidence: 99%
“…ABVD or BEACOPP regimens alone are very effective against blood cancer malignancies, yet, their further development is still needed. Evidence suggests that these regimens could negatively impact the fertility of both male and female patients [ 100 , 101 ]. In addition, Ramos et al reported that the ABVD regimen induces genomic chaos after one year of the treatment.…”
Section: Combination Of Vincristine With Procarbazine or Dacarbazinementioning
confidence: 99%
“…11 Gonadotoxicity and sexual dysfunction are welldocumented for patients with cancer across other tumor types (eg, lymphoma, breast, and germ cell). [12][13][14][15][16][17][18][19][20] However, the population of patients with early-onset CRC differs as rates of sexual dysfunction are higher in CRC (across all age groups, including early-onset CRC) compared with all cancer survivors. 21 This is because of altering physiology as a result of CRC-specific therapies-pelvic radiation, abdominoperineal resection, mesorectal surgery, and cytotoxic chemotherapies.…”
Section: Reproductive Health As An Unmet Need Among Early-onset Crc S...mentioning
confidence: 99%
“…After this regimen, the recovery time of spermatogenesis in men was also much longer. Young patients treated with BEACOPP should be informed of its high gonadotoxicity and directed to a specialist to discuss protective methods to preserve fertility [14][15][16].…”
Section: Abvd Versus Beacoppmentioning
confidence: 99%